KERAGAMAN GENETIK CENDANA (Santalum album Linn) DI KEBUN KONSERVASI EX SITU WATUSIPAT. GUNUNG KIDUL, DENGAN PENANDA ISOSIM - Liliek Haryjanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2009)
Sandalwood (Santalum Album Linn) is one of high economic value foret commodities. However, over exploitation without appropriate rehabilitation has serious degradation of the natural populations caused. Therefore, an ex situ conservation of this species has been established at Watusipat, Gunung kidul in 2000. It comprised of 6 populations collected from East Nusa Tenggara . The genetic diversity of these populations was investigated using isozyme genetic marker with 3 enzymes.Shikimate dehydrogenase (SHD), Esterase (EST), and Diaphorase (DIA). Thirteen alleles were identified on fife polymorphic loci. A relatively high genetic diversity was reflected by paramaters, such as the mean number of alleles per polymorphic locus (A=2.1333); the mean effective number of alleles per polymorphic locus (v= 1.6302); the mean percentage of polymorphic loci (PPL=83.333%); the mean observed heterozygosity (Ho= 0.3951) and the mean expected heterozygosity (HE = 0.3166). Most of genetic diversity (95.62%) was distributed within population. Cluster analysis using UPGMA based on Nei S standard genetic distance reflected two main clusters : Palakahembi, Belu and Soebela constructed the first cluster; whereas Bama, Balela and Helangdohi formed the second cluster.